CSR initiatives by companies for employees through social protection measures - Mohd Salleh, Noor Akma; Muhamad, Rusnah; Mohd Roffeei, Siti Hajar (2017)
Poverty has always been the main concern globally as it alienates and distresses particular groups of citizen that affects their emotion and psychological behaviour, and may have impact on the socioeconomic aspect of the country. Hence, it is critical for the government to address the poverty problem, as this would lead to inequality. One way to minimise income inequality is through the provision of social protection to maintain the basic consumption and living standard of the needed members of the society.The government highlights the importance of increasing involvement of the private sector to improve social protection through their CSR programmes. Thus, the main purpose of this paper is to unearth the concept of social protection and its role in minimising inequality in the society as well as to develop an instrument to measure the social protection dimension of companies’ CSR activities.